DYANMIC ANALYSIS OF SHAPE MEMORY ALLOY OSCILLATORS IN ACTIVE SUSPENSION SYSTEM (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
Smart materials have a growing technological importance due to their unique thermomechanical characteristics. Shape memory alloys belong to this class of materials being easy to manufacture, relatively lightweight, and able to produce high forces or displacements with low power consumption. These aspects could be exploited in different applications including vibration control. A dynamic vibration absorber (DVA) can be used as an effective vibration control device. It is essentially a secondary mass, attached to an original system via a spring and damper. The natural frequency of the DVA is tuned such that it coincides with the frequency of unwanted vibration in the original system. This work aims to develop a dynamic vibration absorber with the help of shape memory alloy (SMA) springs in order to attenuate the vibration for a range of excitation frequencies. The experimental apparatus consisted of low-friction cars free to move in a rail. A shaker that provides harmonic forcing excites the system. Special attention is dedicated to the analysis of vibration reduction that can be achieved by considering different approaches exploiting temperature variations promoted either by electric current changes or by vibration absorber techniques. The results established that adaptability due to temperature variations is defined by modulus of stiffness